Conservation agriculture in Morocco: review and analysis for the resilience of the cereal system on 1 million hectares by 2030 - Moussadek, Rachid; Laghrour, Malika; Kadiri, Kenza; Mrabet, Rachid (2024)
Morocco, like other North African countries, is located in an area qualified as a hotspot in terms of climate change. This phenomenon is associated with degradation of agricultural land due to intrinsic soil conditions and intensive plowing coupled with poor agricultural practices increasingly reducing the fertility of these soils and their productivity. Over the past decades, several research studies carried out in Morocco have proposed alternatives based on conservation agriculture, in particular direct seeding. This system aims to stabilize yields of main crops (cereals, legumes, oilseeds, etc.) by improving water use efficiency and soil fertility. Indeed, direct seeding conserves moisture in the soil (adaptation), improves soil carbon sequestration (mitigation) and increases yields (productivity). This system therefore constitutes a resilient measure in the face of climate change. This led the Department of Agriculture to adopt a roadmap to promote this system over 1 million ha as part of the Generation Green 2020-2030 strategy. This chapter summarizes (i) the main research findings on this system in relation to soil health and water management, (ii) the major advantages in relation to crop diversification and productivity, (iii) ) the challenges to be raised to ensure its dissemination among farmers in Morocco and (iv) finally present the vision of the national program to promote direct seeding on 1 Million Ha by 2030.